Phase formation and dielectric properties of Ba0.9Sr 0.1[Ti1-x(Fe0.5Nb0.5) x]O3 ceramics - Sukum Eitssayeam (2018)
In this work, the complex perovskite Ba0.9Sr0.1[Ti1-x(Fe0.5Nb0.5)x]O3(BST-FN) ceramic system with x = 0.0, 0.1, 0.2, 0.3, 0.4 and 0.5 were synthesized via a solid state reaction method. The ceramics were subsequently examined at room temperature by Xray diffraction using Cu Karadiation to identify the phase composition of each sample. The structures of the samples were found to be tetragonal and the tetragonality of which decreased with increasing the FN content. The relative permittivity and loss tangent were found to increase with temperature. The highest εrwas 2941 with the tan ∞ of 0.713 for x = 0.2 at room temperature and at 1 kHz. Copyright © Taylor &Francis Group, LLC.